Optimasi Produksi Selulosa Mikrokristal dari Selulosa Tandan Kosong Kelapa Sawit Menggunakan Metode Respon Permukaan - Serarifi Elagin Harahap; Michelle Michelle; Silva Latisya; Firda Dimawarnita; Tjahjono Herawan; Yora Faramitha (Jurnal Penelitian Kelapa Sawit, 2025)
Oil palm empty fruit bunches (OPEFB) are abundant biomass waste with high cellulose content, yet their utilization is limited to conventional applications such as mulch in palm oil plantations. However, OPEFB can be potentially developed into high-value derivative products, such as microcrystalline cellulose (MCC), which has widespread applications across various industries, including pharmaceuticals, food, and composite materials. This study aims to optimize MCC production from OPEFB cellulose through acid hydrolysis using the Response Surface Methodology (RSM) approach to achieve the highest yield. Optimization was conducted on three main variables: hydrochloric acid (HCl) concentration (1, 2, 3 M), hydrolysis time (20, 40, 60 minutes), and the mass ratio of cellulose to HCl volume (25, 50, 75 g/L), using a Box-Behnken experimental design. The results showed that the highest MCC yield of 84.41% was achieved at an HCl concentration of 1.77 M, a hydrolysis time of 36.57 minutes, and a cellulose mass ratio to the HCl volume of 58.33 g/L. The MCC obtained under optimal conditions has an alpha cellulose content of 71.42%; hemicellulose 14.36%; and lignin 0.59%. Fourier Transform Infrared (FT-IR) and X-Ray Diffraction (XRD) analyses confirmed spectral profiles and crystallinity consistent with typical MCC. The results demonstrate that production optimization using RSM successfully improved MCC production efficiency with high yield and cellulose content.